1984
DOI: 10.1021/jo00177a006
|View full text |Cite
|
Sign up to set email alerts
|

Alkylation of allylic derivatives. 8. Regio- and stereochemistry of alkylation of allylic carboxylates with lithium methylcyanocuprate

Abstract: 0.075 g, 0.18 mmol) was trichloroacetylated as above to yield pure cis complex in 97% yield following column chromatography, eluting with 5% ether/petroleum ether: IR (CS2) 2100, 2060, 2040 cm"1 (metal carbonyl), 1770 cm'1 (OCOCCl3); 1H NMR (CS2) 6.1 (s, 1 H, complexed acetylenic), 4.7 (br m, w1/2 = 12 Hz, CHOH), 1.7-2.22 (br m, 9 H, ring + OH).Acknowledgment. We are grateful for financial support provided by the Public Health Service (GM 26760).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…We finally applied these 6 NHC ligands to a copper-catalyzed allylic arylation of cinnamyl bromide with PhMgBr to evaluate the influence of the structure on catalytic activity. Mechanistically, a bulky and electron-deficient ligand is thought to be preferable because it heightens S N 2′ selectivity . Our group previously found that the DHASIMeCuCl complex, which forms in situ, generates S N 2′-substituted products as its major yield (S N 2:S N 2′ = 20:80), whereas IMeCuCl gave us a 1:1 mixture of S N 2 and S N 2′ substituted products.…”
Section: Resultsmentioning
confidence: 99%
“…We finally applied these 6 NHC ligands to a copper-catalyzed allylic arylation of cinnamyl bromide with PhMgBr to evaluate the influence of the structure on catalytic activity. Mechanistically, a bulky and electron-deficient ligand is thought to be preferable because it heightens S N 2′ selectivity . Our group previously found that the DHASIMeCuCl complex, which forms in situ, generates S N 2′-substituted products as its major yield (S N 2:S N 2′ = 20:80), whereas IMeCuCl gave us a 1:1 mixture of S N 2 and S N 2′ substituted products.…”
Section: Resultsmentioning
confidence: 99%
“…[4] Notably, no significant differences were seen between runs using preformed complex 6 and tests carried out with the catalyst obtained from 1 in situ (entries 1 and 2); this observation justified the use of catalysts generated in situ. [4,6,[20][21][22][23][24][25][26][27][28] In these two possible pathways, a bulky ligand should accelerate the reductive elimination step leading to the γ-product. The proportion of branched product increased in the order 1Ͻ 2 Ͻ 3 Ͻ 4, with the b/l ratios varying from 22:78 for 1 to 78:22 for 4 (entries 1-4).…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] Being applicable to the formation of carbon-carbon, carbon-nitrogen, and carbon-oxygen bonds, it has become very popular in the field of natural product synthesis as well as in biomolecular and medicinal chemistry. Interestingly, allylic substitution with this particular metal arylated compounds in variable proportions, with the b/l ratio being the highest (78: 22) for the most crowded imidazolium salt used, namely that in which the second nitrogen atom (N2) was substituted by a mesityl group. The nucleophilic attack can lead to two compounds, the S N 2-product (or α-product) or the S N 2Јproduct (or γ-product), with regiocontrol of the reaction depending on various factors, such as the leaving group, the nature of the solvent, and the catalytic ligand-metal combination.…”
Section: Introductionmentioning
confidence: 96%
“…This can be attributed to a back donation of the filled d 10 orbitals of the Cu atom into the s* orbital of the OPiv group, [39] the extent of which is determined by the nature of the leaving group and the steric resistance. [40][41][42][43] The dihedral angle of C2 À C1 À Cu À C4 is 173.68 in 3-O and 155.78 in 3, respectively. Clearly, this rotation of the dihedral angle can be attributed to the electrostatic attraction between the OPiv group and the Cu group.…”
Section: Resultsmentioning
confidence: 99%